Selecting the Appropriate First-Line Strategy Based on Hyperdense Vessel Sign in Acute Ischemic Stroke Increases First Pass Recanalization: A Tertiary Center Experience - Kovilapu, Uday Bhanu; Jain, Narendra; Mishra, Atul; Malik, Virender (Indian Journal of Radiology and Imaging, 2021)
Background: The data pertaining to selecting an optimal first-line strategy (stent retriever [SR] vs. contact aspiration [CA]) based on noncontrast computed tomography (NCCT) in cases of acute ischemic stroke consequent to large vessel occlusion (LVO) is lacking.Aims: This article studies the influence of hyperdense vessel sign (HVS) in selecting optimal first-line strategy, with intention of increasing first-pass recanalization (FPR).Methods: Upfront approach at our center is SR technique with rescue therapy (CA) adoption consequent to three failed SR attempts to achieve successful recanalization. Data of patients with acute LVO who underwent mechanical thrombectomy from June 2017 to May 2020 was retrospectively analyzed. Patients were classified into HVS (+) and HVS (−) cohort. Rate of successful recanalization (first pass, early, and final) and efficacy of rescue therapy was assessed between the two cohorts.Results: Of 52 patients included, 28 and 24 were assigned to the HVS (+) and HVS (−) cohort, respectively. FPR was observed in 50% of HVS (+) and 20.9% of HVS (−) (p = 0.029). Early recanalization was documented in 64.2% of HVS (+) and 37.5% of HVS (−) (p = 0.054). Rescue therapy need was higher in patients not demonstrating HVS (p = 0.062). Successful recanalization was achieved with rescue therapy in 50% of HVS (−) group.Conclusion: A higher FPR is achievable following individualized first-pass strategy (based on NCCT appearance of clot), instead of a generalized SR first-pass approach. This CT imaging-based strategy is a step closer to achieving primary angiographic goal of FPR.
Keywords: first-line strategy; hyperdense vessel sign